Mengatasi Kecemasan Ibu Hamil Menjelang Persalinan dengan Terapi Komplementer - Lina Contesa; Tri Restu Handayani (Natural: Jurnal Pelaksanaan Pengabdian Bergerak bersama Masyarakat., 2025)
Background: Anxiety before childbirth is a psychological disorder often experienced by pregnant women, especially in the third trimester of pregnancy. Fear of pain, worry about the condition of the fetus, and uncertainty about the delivery process are the main triggering factors. If not handled properly, this anxiety can have serious consequences, such as increased stress hormones (cortisol), sleep disorders, high blood pressure, and even labor complications. Therefore, interventions are needed that not only focus on physical aspects, but also support mental and emotional balance. Objective: The purpose of this activity is to provide education and practical training to pregnant women on anxiety management before childbirth through the application of complementary therapies, and to evaluate the effectiveness of this approach in increasing the readiness and calmness of participants. Method: The activity was carried out at PMB Lismarini, Tulungagung, involving 20 pregnant women in their third trimester. Education was carried out interactively using visual media and group discussions. Next, participants participated in the practice of three types of complementary therapies: (1) deep breathing relaxation with diaphragmatic breathing techniques, (2) aromatherapy using lavender as a relaxation agent, and (3) classical music with a slow rhythm played during the session. Results: This activity showed positive results. Eighty-five percent of participants experienced an increase in knowledge scores after the educational session, and 60% showed a significant decrease in anxiety levels based on questionnaire results. Most participants also reported feeling calmer, more prepared, and more confident in facing childbirth. The satisfaction rate with the activity reached 90%, indicating that the methods implemented were well-received by participants. Conclusion: Complementary therapy combined with education is effective in helping pregnant women manage anxiety before childbirth. This activity emphasizes the importance of a holistic approach to antenatal care.